Less Invasive Left Ventricular Assist Device Implantation Is Safe and Reduces Intraoperative Blood Product Use: A Propensity Score Analysis VAD Implantation Techniques and Blood Product Use. Issue 1 (11th May 2020) - Riebandt, Julia; Schlöglhofer, Thomas; Moayedifar, Roxana; Wiedemann, Dominik; Wittmann, Franziska; Angleitner, Philipp; Dimitrov, Kamen; Tschernko, Edda; Laufer, Günther; Zimpfer, Daniel
Abstract : Despite increasing popularity and multiple postulated benefits, less invasive (LIS) left ventricular assist device (LVAD) implantation has not been sufficiently compared with standard full sternotomy (FS). We report the outcomes of a propensity score analysis designed to compare LIS and FS LVAD implantation, with perioperative blood product use, adverse event rates, and mortality as primary objective. From September 2010 to August 2016, 159 consecutive patients received a Medtronic HVAD or Abbott HeartMate 3 LVAD via a FS or LIS approach. Outcomes were analyzed using proportional hazard Cox regression, with risk adjustment based on a LIS approach propensity score model computed from demographics, risk factors, and operative covariates. Seventy-five patients were matched and compared (HVAD 83% [n = 62]; LIS approach 43% [n = 32]; mean age 60 ± 12 years; 89% [n = 67] male; 48% [n = 36] ischemic cardiomyopathy [ICMP]; 37% [n = 28]). Patient groups were comparable with regard to preoperative patient characteristics. Less invasive LVAD implantation was successful in all patients with no intraoperative conversions. In-hospital mortality was 16% in both groups, despite 37% Interagency Registry for Mechanically Assisted Circulatory Support Level I patients. Overall, 28% of the LIS patients did not receive any blood products intraoperatively, whereas, in the FS group, only two patients (5%) did not require the administration of blood products ( p = 0.000). This was also a significant finding in the overall perioperative phase in which seven LIS patients (22%) who not receive any blood products versus two FS patients (5%; p = 0.033). Otherwise, outcomes were comparable. Less invasive LVAD implantation is a feasible, safe, and reduces blood product use.